Response of short rotation forestry to dairy farm-pond effluent irrigation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Agricultural Engineering at Massey University - Peña Obando-Tungcul, Rebecca dela (Massey University, 1999)
A growing concern to protect the environment has prompted Regional Councils in New Zealand to monitor compliance under the Resource Management Act (1991) covering the discharge of wastewater into waterways. To meet the desired standards, application of wastewater onto high dry matter producing short vegetation forests offers opportunity for the beneficial use of nutrients while renovating the wastewater. A field trial was established near Palmerston North to determine the response of nine Salix clones and one Eucalyptus short rotation forest (SRF) species to dairy farm effluent irrigation and to determine their water and nutrient uptake potential. A micro sprinkler irrigation system was designed to operate at 100 kPa and supply each plot of 16 trees with either 7.5 mm. 15 mm, or 30 mm of dairy farm effluent every two weeks. Twenty-four applications were made covering two growing seasons with a break over winter. A control treatment of 7.5 mm of water + 187.5 kg N haˉ¹ yearˉ¹ was included, being equivalent to the nitrogen addition from the lowest effluent application rate. The three SRF species, Salix matsudana x alba (NZ 1295). Salix kinuyanagi (PN 386) and Eucalyptus nitens were selected for more detailed analysis than the other seven Salix clones. This included the measurement of evapotranspiration rates and a pot trial to determine the tolerance level of seedlings to higher levels of effluent application. Application of up to 90 mm of effluent per fortnight increased the biomass production and nutrient accumulation of potted PN 386 and E. nitens. whereas the NZ 1295 produced optimum biomass and accumulation of nutrients at 60 mm of effluent application per fortnight. At the end of the first growing season, the above ground biomass of the ten tree species in the field trial was assessed using a non-destructive method followed by a destructive harvest at the end of the second growing season. Dry matter production in these short rotation forest crops varied with species and clones and with the amount of dairy farm-pond effluent applied. Salix NZ 1296. PN 386 and NZ 1295 irrigated with the highest application rate of 30 mm of effluent per fortnight produced the highest biomass yields of 37.91, 37.87 and 37.58 ODt haˉ¹ yearˉ¹ respectively. NZ 1296 irrigated with 30 mm of effluent per fortnight accumulated 196 kg N haˉ¹ yearˉ¹, 37.6 kg P haˉ¹ yearˉ¹, and 103.6 kg Mg haˉ¹ yearˉ¹ in its above ground biomass. E. nitens irrigated with 15 mm of effluent per fortnight produced a comparable above ground oven dry biomass yield of 36.33 ODt haˉ¹ yearˉ¹ and accumulated the highest amount of potassium and calcium in its above ground biomass giving 145.4 and 148.1 kg haˉ1 yearˉ¹, respectively. Transpiration monitoring during the second growing season using a heat pulse technique showed that under the highest application rate (30 mm per fortnight) on a cloud-free day. 15 month old NZ 1295 trees each transpired the highest cumulative amount of 6.38 mm day ˉ¹ compared to 2.71 mm dayˉ¹ for trees irrigated at the lowest rate (7.5 mm per fortnight). Results of this study overall suggest that increasing the rate of effluent irrigation will increase the soil pH. nitrates and exchangeable potassium, calcium and magnesium concentrations throughout the soil profile. Total nitrogen and total phosphorus levels decreased throughout the soil profile after the second growing season. The cation exchange capacity of the soil decreased with increased rate of effluent after the second growing season. The soil-SRF treatment system renovated the nutrients in the effluent. The soil-E. nitens treatment system renovated the highest percentage of total nitrogen (17.21t haˉ¹ mˉ¹ depth) equivalent to 96.45% of total nitrogen supplied by both the soil and the 30 mm of effluent applied per fortnight. The soil-PN 386 treatment system renovated the highest percentage of total phosphorus (6.4 t haˉ¹ mˉ¹ depth) equivalent to 92.72% of the total phosphorus available in the soil and supplied by the 7.5 mm of effluent treatment. The soil-NZ 1295 treatment system renovated the highest percentage of potassium (99.5%). calcium (98.74%) and magnesium (95.63%) supplied by both the soil and the 30 mm of effluent treatment. The capacity of the three SRF species to renovate total nitrogen, phosphorus and potassium from the effluent decreased with increasing rates of application. PN 386 irrigated at 7.5 mm of effluent renovated the highest percentage of 99.45% of total nitrogen (114.25 kg haˉ¹ over two growing seasons) and 79.18% of total phosphorus (35.60 kg haˉ¹ over two growing seasons). The amounts of calcium and magnesium renovated by the SRF species were more than the amount supplied by even the highest rate of effluent (30 mm per fortnight). Salix PN 386. NZ 1295 and E. nitens are recommended SRF species to grow in a land treatment scheme for dairy farm pond-effluent when applied at a rate of 30 mm per fortnight over the growing period on to a silt loam soil. Pot trials showed higher volumes of effluent renovation on to PN 386 and E. nitens may be applicable when applied up to 90 mm of effluent per fortnight but further evaluation is needed before this can be recommended.
Keywords: Dairy waste; Dairy farms Waste disposal; Sewage disposal ground; Forests forestry; Organic wastes fertilizer; New Zealand; Environmental aspects; Management